2010
DOI: 10.1007/s00415-009-5438-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, prognosis, and seropositivity to the anti-aquaporin-4 antibody in Korean patients with longitudinally extensive transverse myelitis

Abstract: Longitudinally extensive transverse myelitis (LETM) is a syndrome with extensive spinal cord lesions spanning three or more vertebral segments on spinal cord MRI. Although many reports have indicated that LETM is a characteristic feature of neuoromyelitis optica (NMO) in Western countries, the clinical characteristics and risk for development of NMO in Korean patients with LETM is not clear. We retrospectively investigated the clinical, laboratory, radiological features, and prognosis of Korean patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
18
1
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 19 publications
(24 reference statements)
7
18
1
14
Order By: Relevance
“…Idiopathic ATM on MRI is characterized by a centrally located high T2 signal lesion occupying more than two-thirds of the cross-sectional area of the cord, greater than three vertebral segments in length, with a predilection for the thoracolumbar cord [23,24]. The present study showed some deviations from these reports in the clinical profiles of Chinese patients with idiopathic ATM: (1) M-ATM was found in only 31.0% (9/29) of idiopathic ATM patients, while R-ATM was common (69.0%, 20/29); (2) there was no peak age of onset between 10 and 19 years; (3) female predominance in R-ATM was different from other reports [25][26][27]; (4) spinal lesions occupying more than two-thirds of the cross-sectional area of the cord were rare, and only 11.1% (1/9) M-ATM patients and 15.0% (3/20) R-ATM had holocord lesions.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Idiopathic ATM on MRI is characterized by a centrally located high T2 signal lesion occupying more than two-thirds of the cross-sectional area of the cord, greater than three vertebral segments in length, with a predilection for the thoracolumbar cord [23,24]. The present study showed some deviations from these reports in the clinical profiles of Chinese patients with idiopathic ATM: (1) M-ATM was found in only 31.0% (9/29) of idiopathic ATM patients, while R-ATM was common (69.0%, 20/29); (2) there was no peak age of onset between 10 and 19 years; (3) female predominance in R-ATM was different from other reports [25][26][27]; (4) spinal lesions occupying more than two-thirds of the cross-sectional area of the cord were rare, and only 11.1% (1/9) M-ATM patients and 15.0% (3/20) R-ATM had holocord lesions.…”
Section: Discussioncontrasting
confidence: 82%
“…Three western studies reported that idiopathic R-ATM was different from classical MS [25,27,32], and recurrent longitudinal extensive myelitis (RLEM), with high serum positive rate for NMO-IgG antibodies was included in the NMO spectrum [29]. In contrast, in Asia, idiopathic R-ATM without extra-spinal lesions may be considered as spinal MS [33], and RLEM was different from spinal-restricted NMO [26,34]. Therefore, the nosology of idiopathic R-ATM remains controversial.…”
Section: Discussionmentioning
confidence: 84%
“…None of the seronegative LETM patients experienced a second relapse. Other authors have also reported a low percentage of positive NMO-IgG antibodies in patients presenting with LETM [21,22,23]. Nonetheless, a recent study evaluating LETM patients in an international reference center reported that almost 60% of cases presented antibodies against aquaporin-4 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Male predominance in seronegative LETM has been highlighted in earlier studies too. [19] These patients may represent a heterogeneous group, and some patients may have other unidentified antigenic targets in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%